Nonlinear science and complexity - Machado, J. A. Tenreiro (Springer, 2011)
This book contains selected papers of NSC08, the 2nd Conference on Nonlinear Science and Complexity, held 28-31 July, 2008, Porto, Portugal. It focuses on fundamental theories and principles, analytical and symbolic approaches, computational techniques in nonlinear physics and mathematics. Topics treated include Chaotic Dynamics and Transport in Classic and Quantum Systems Complexity and Nonlinearity in Molecular Dynamics and Nano-Science, Complexity and Fractals in Nonlinear Biological Physics and Social Systems, Lie Group Analysis and Applications in Nonlinear Science, Nonlinear Hydrodynamics and Turbulence Bifurcation and Stability in Nonlinear Dynamic Systems, Nonlinear Oscillations and Control with Applications, Celestial Physics and Deep Space Exploration, Nonlinear Mechanics and Nonlinear Structural Dynamics, Non-smooth Systems and Hybrid Systems Fractional dynamical systems.